Production of ethanol from starch by free and immobilized Candida tropicalis in the presence of alfa-amylase - Jamai, L.; Ettayebi, K.; El Yamani, J.; Ettayebi, M.
Candida tropicalis is a potentially useful organism for the commercial production of ethanol as it is capable of fermenting starch at a low rate. To enhance this carbon source utilization and increase the rate of alcohol production, we pretreated corn soluble starch with alpha-amylase. Starch liquefaction was sufficient to drive the fermentation and to convert 96 percent substrate to ethanol. Indeed, in the presence of exogenous alpha-amylase, 9 percent (w/v)soluble starch was converted to 43.1g ethanol/l in 65 h with a productivity of 0.65 g/l h. Thus, bio-ethanol production using free and calcium alginate-immobilized C. tropicalis does not require the saccharification step. Furthermore, fed-batch fermentation by free C. tropicalis cells increased the final concentration to 56 g ethanol/l, reaching published values for Saccharomyces cerevisiae recombinant strains expressing both alpha-amylase and glucoamylase.
Keywords: STARCH FERMENTATION; CANDIDA TROPICALIS; ETHANOL PRODUCTION; CELL IMMOBILIZATION